СОВРЕМЕННОЕ РАЗВИТИЕ ДЕТСКО-ЮНОШЕСКОГО ТУРИЗМА В АЛТАЙСКОМ КРАЕ - Н.Г. Прудникова; И.С. Кротова (Siberian Journal of Tourism and Economic, 1970)
Рассмотрено современное состояние детско-юношеского туризма в Алтайском крае и возможности дополнительного образования детей. Развитие данного вида туризма способствует формированию основ здорового образа жизни детей через туризм и краеведение.The article discusses current state of tourism for children and youth in Altai region, and possibilities of additional education for children. Development of this type of tourism promotes development of healthy lifestyle in children through outdoor recreation and studies of local history and geography.